Analisis Dampak Keberadaan Angkutan Daring Terhadap Perubahan Pendapatan Sopir Angkutan Kota di Kota Surabaya (Studi Kasus Pendapatan Sopir Angkutan Kota di Terminal Dukuh Kupang Surabaya) - Hardany Praciwi, Ruwita Kusuma; Pratomo, Gigih (Economie: Jurnal Ilmu Ekonomi, 2020)
This study is to determine the impact of online transportation on the income of city transport drivers at Dukuh Kupang terminal in Surabaya City and to find out solutions to increase the income of city transport drivers at Dukuh Kupang Terminal in Surabaya City. The method used in this research uses qualitative research methods. The analysis technique used in this research is case study ethnography which is used to analyze data from documentation, observation, and interviews by describing or describing the data collected from Dukuh Kupang Terminal, Surabaya City. The existence of online transportation has an impact on decreasing the welfare and income of city transportation drivers at Dukuh Kupang Surabaya Terminal. Cooperation in the transportation sector with the education sector is an alternative solution to increase the welfare level of city transportation drivers.